APPLICATION PROCEDURES AND ACCOUNTING SYSTEM OF FIXED ASSETS IN ACCORDANCE PERMENDAGRI NO.17 YEAR 2007 DEPARTMENT OF EDUCATION MANADO CITY - Yanis, Irene Sutri; Kalangi, Lintje; Pusung, Rudy J. (FEB Universitas Sam Ratulangi Manado, 2015)
Regional autonomy requires local governments to provide public services which are based on the principles of public service including: transparency, accountability, conditional, participatory, equal rights, the balance of rights and obligations for the creation of good governance. Evaluation of the implementation of accounting systems and procedures for fixed assets is one component of the resources that are critical to the achievement of Good Governanace. Intangible fixed assets are assets that have a useful life of more than twelve months for use in government operations or used by the general public. The purpose of this study is to know the system and procedures of the fixed asset accounting based on Act No. 17 of 2007, as well as the effectiveness of the implementation of the system and procedures of the fixed asset accounting according to Act No. 17 of 2007 in the Department of Education of Manado City. The method used in this research is descriptive. Data are obtained through field studies. The results shows that the System and Procedures of the fixed asset accounting that have been implemented by the Department of Education has run well, including planning, procurement, utilization, maintenance, removal, and transfer of assets. It is recommend that the systems and procedures of assets in Manado City Department of Education are completed or perfected in accordance with the systems and procedures in Act No.17 of 2007. Keywords: systems and procedures, fixed asset accounting, effectivenesse